A new porphyrinic vanadium-based MOF constructed from infinite V(OH)O4 chains: syntheses, characterization and photoabsorption properties. (10th December 2021) - Nguyen, My V.; Dong, Hieu C.; Truong, Vy T. N.; Nguyen, Hung N.; Luu, Loc C.; Dang, Nam N.; Nguyen, Tuyet A. T.
Abstract : A new porphyrinic vanadium-based metal–organic framework (MOF), namely V-MOF-10 [V2 (OH)2 (H2 TCPP)], constructed from {V(OH)O4 }∞ chains and 4-tetracarboxyphenylporphyrin linkers, was synthesized by a solvothermal procedure. Abstract : A new porphyrinic vanadium-based metal–organic framework (MOF), namely V-MOF-10 [V2 (OH)2 (H2 TCPP)], constructed from {V(OH)O4 }∞ chains and 4-tetracarboxyphenylporphyrin linkers, was synthesized by a solvothermal procedure. Structural analysis indicated that V-MOF-10 possesses orthorhombic symmetry featuring two types of pores (5.2 × 11.9 Å and 3.5 × 11.9 Å). Full characterization of V-MOF-10 was performed by powder X-ray diffraction (PXRD), Fourier transform infrared (FT-IR), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and elemental analysis (EA). The N2 isotherm of V-MOF-10 at 77 K shows a reversible uptake and permanent porosity with a high BET (Langmuir) surface area of 1477 m 2 g −1 (1553 m 2 g −1 ). The optical band gap of V-MOF-10, measured by UV-vis diffuse reflectance spectroscopy, is calculated to be 1.71 eV, resulting in a shift of absorption wavelength to the visible light region. Furthermore, our density functional theory (DFT) calculations confirm an acceptable correspondence of the band gap value with the mentioned experimental investigation, similar to the incorporated experimental and theoretical observations in the previous literature. Remarkably, V-MOF-10 exhibits an excellent photocatalytic property of organic dyes with the degradation efficiency of 100% for methylene blue (MB) and 89% for methylene orange (MB) after 120 min under illumination by visible light. These results suggest that V-MOF-10 could be used as a promising candidate in further photocatalytic studies.